Multimaterial fiber electronics via convergence thermal drawing and cold drawing - Wang, Zhixun (Nanyang Technological University, 2021)
Fibers are in every aspect of human life. However, they have surprisingly evolved less in technological functions to date. With outstanding mechanical flexibility and structural robustness, fibers are promising candidates in electronics. The realization of fiber electronics requires a challenging integration of multiple materials. Among varying approaches, thermal drawing can produce multimaterial fibers with sophisticated structures at an extended length. However, it requires all selected materials to soften or melt into viscous flows with matched viscosities at drawing temperature. This thesis addresses the challenges of co-drawing soft polymers and solid materials that do not soften or melt in the process via convergence thermal drawing. Monolithic fiber photodetector is demonstrated. Further, we utilize the mechanical mismatch between the different materials to create in-fiber structures by cold drawing. We also extend the study of this intriguing mechanical instability to two-dimensional materials/polymer composites and demonstrate a simple yet effective tool for nanomaterials structuring.